Reconstructing Qur'anic Social Justice for the Empowerment of Marginalized Communities: Integrating Social and Feminist Exegesis - Nurkholis (Attractive : Innovative Education Journal, 2025)
Contemporary forms of marginalization including structural inequality, gender discrimination, and social exclusion have challenged conventional interpretations of Qur'anic social justice to respond more effectively to changing social realities. While previous studies have examined social justice through either social or feminist exegesis, limited attention has been given to integrating these interpretative approaches within a single ethical framework. This study aims to reconstruct Qur'anic social justice as an ethical foundation for empowering marginalized communities by integrating insights from social and feminist exegesis. Employing a qualitative library research design with a conceptual approach, the study draws upon the Qur'an, classical and contemporary Qur'anic commentaries, scholarly books, and peer-reviewed journal articles. The collected literature was analyzed through conceptual analysis, comparative interpretation, thematic synthesis, and conceptual reconstruction. The findings indicate that Qur'anic social justice extends beyond legal and distributive understandings by integrating the ethical principles of 'adl (justice), qisṭ (equity), karāmah (human dignity), raḥmah (compassion), and musāwah (equality). The study further argues that social and feminist exegesis are complementary rather than competing approaches, offering a more comprehensive understanding of structural, cultural, and gender-based marginalization. This integrative reconstruction broadens contemporary discussions of Qur'anic social justice and provides an ethical foundation for more inclusive approaches to Islamic education, community empowerment, and social development.